A case study of spinal nerve compression caused by a small amount of epidural pneumatosis. (26th July 2018) - Zhang, Ke; Yu, Mingshuai
This case describes a patient with painless childbirth in anaesthesia recovery, who suffered from spinal nerve dysfunction because of the presence of a small amount of epidural gas. Although the patient eventually recovered, this reminds us that timely observation and treatment is important in clinical epidural anaesthesia.